Executive functions scale for university students: UEF-1 - Ramos-Galarza, Carlos; Ramos, Valentina; Del Valle, Milenko; Lepe-Martínez, Nancy; Cruz-Cárdenas, Jorge; Acosta-Rodas, Pamela; Bolaños-Pasquel, Mónica (Frontiers in Psychology, 2023)
Introduction Executive functions are a set of mental abilities that allow human beings to consciously regulate their behavior and, in a university setting, will have a significant impact on student success during professional training. Objective To develop a scale to assess executive functions in a university setting. Method Using a sample of 1,373 university students from Chile (663) and Ecuador (710) between 17 and 33 years old (Mage = 20.53, SD = 2.34). A study was carried out to analyze the psychometric properties of the instrument using a reliability and validity analysis for a scale that assesses executive functions: conscious monitoring of responsibilities, supervisory attentional system, conscious regulation of behavior, verification of behavior to learn, decision making, conscious regulation of emotions, and management of elements to solve tasks. Results Adequate internal consistency parameters were found between α = 0.71 and 0.85. The seven executive functions proposed on the scale correlated proportionally between r = 0.42 and 0.62. In the confirmatory factor analysis, good fit indices were obtained in the model of the seven executive functions x2(413) = 1649.14, p = <0.001, CFI = 0.91, SRMR = 0.04 and RMSEA = 0.04. Discussion The research carried out reaches its conclusion stating that the scale that was developed has the psychometric properties to assess executive functions in the Latin American setting. The results regarding previous research and the contribution made in the line of research of executive functions are discussed.